DDRE-05. LONG-TERM OUTCOME OF INTRATHECAL CHEMOTHERAPY WITH PEMETREXED IN LEPTOMENINGEAL METASTASIS FROM NON-SMALL CELL LUNG CANCER WITH EGFR-MUTATION: A CASE REPORT. (12th November 2021) - Wang, hui; Zhou, Jiangfen; Wen, Lei; Hong, Weiping; Cai, Linbo
Abstract: Leptomeningeal metastasis (LM) is fatal complication of non-small cell lung cancer (NSCLC), which has a poor prognosis and lacks effective treatments. Pemetrexed, a multitargeted antifolate agent, has demonstrated antitumor activity, a few studies have shown intrathecal pemetrexed (IP) controllable toxicities and potential promising efficacy for LM from NSCLC patients. We report a patient who diagnosed with LM from NSCLC harboring epidermal growth factor receptor (EGFR) mutation in exons 21 via typical neurological symptoms, magnetic resonance imaging (MRI) and positive cerebrospinal fluid (CSF) cytology. The curative effect of tyrosine kinase inhibitor (TKI) targeted drugs was maintained for a short time, the first-generation TKI icotinib was 4 months, and the third-generation osimertinib was 4 months. Then the patient received IP, and osimertinib continued. 30 mg of pemetrexed were implemented on day 1 every weeks for 8 weeks via lumbar puncture, then 50 mg of pemetrexed on day 1 every 4 week for 8 times. This treatment regimen resulted in the alleviation of the neurological symptoms, the CSF level of carcinoembryonic antigen also decresed without obvious side effects. At the time of this manuscript's submission, she had maintained stable disease (SD) for more than 11 months. To our knowledge, this study provides the first clinical evidence that longterm intrathecal chemotherapy with pemetrexed providing a therapeutic approach against LM from NSCLC.